Schizophrenia at a genetics crossroads: Where to now? - CORVIN, AIDEN (My University, 2013)
These are interesting times for schizophrenia genetics. The last 5 years has seen unprecedented progress, moving us from debate about putative genetic models to an understanding that susceptibility involves a complex interplay of both common and rare genetic risk variants. Critical advances, achieved through the confluence of high-throughput genomics platforms and unparalleled collaboration (eg, the Psychiatric Genomics Consortium),1 have been the subject of excellent reviews elsewhere.2–4 The focus of this article is on a fresh challenge. How to move past gene discovery to understand pathophysiology and disease etiology?
PUBLISHED
Keywords: schizophrenia genetics; schizophrenia genetics; Genes & Society; Neuroscience